Increased Ca buffering underpins remodelling of Ca2+ handling in old sheep atrial myocytes. (11th September 2017) - Clarke, Jessica D.; Caldwell, Jessica L.; Pearman, Charles M.; Eisner, David A.; Trafford, Andrew W.; Dibb, Katharine M.
Abstract : Key points: Ageing is associated with an increased risk of cardiovascular disease and arrhythmias, with the most common arrhythmia being found in the atria of the heart. Little is known about how the normal atria of the heart remodel with age and thus why dysfunction might occur. We report alterations to the atrial systolic Ca 2+ transient that have implications for the function of the atrial in the elderly. We describe a novel mechanism by which increased Ca buffering can account for changes to systolic Ca 2+ in the old atria. The present study helps us to understand how the processes regulating atrial contraction are remodelled during ageing and provides a basis for future work aiming to understand why dysfunction develops. Abstract: Many cardiovascular diseases, including those affecting the atria, are associated with advancing age. Arrhythmias, including those in the atria, can arise as a result of electrical remodelling or alterations in Ca 2+ homeostasis. In the atria, age‐associated changes in the action potential have been documented. However, little is known about remodelling of intracellular Ca 2+ homeostasis in the healthy aged atria. Using single atrial myocytes from young and old Welsh Mountain sheep, we show the free Ca 2+ transient amplitude and rate of decay of systolic Ca 2+ decrease with age, whereas sarcoplasmic reticulum (SR) Ca content increases. An increase in intracellular Ca buffering explains both the decrease in Ca 2+ transient amplitude and decay kinetics in the absence of any change in sarcoendoplasmic reticulum calcium transport ATPase function. Ageing maintained the integrated Ca 2+ influx via I Ca‐L but decreased peak I Ca‐L . Decreased peak I Ca‐L was found to be responsible for the age‐associated increase in SR Ca content but not the decrease in Ca 2+ transient amplitude. Instead, decreased peak I Ca‐L offsets increased SR load such that Ca 2+ release from the SR was maintained during ageing. The results of the present study highlight a novel mechanism by which increased Ca buffering decreases systolic Ca 2+ in old atria. Furthermore, for the first time, we have shown that SR Ca content is increased in old atrial myocytes. Key points: Ageing is associated with an increased risk of cardiovascular disease and arrhythmias, with the most common arrhythmia being found in the atria of the heart. Little is known about how the normal atria of the heart remodel with age and thus why dysfunction might occur. We report alterations to the atrial systolic Ca 2+ transient that have implications for the function of the atrial in the elderly. We describe a novel mechanism by which increased Ca buffering can account for changes to systolic Ca 2+ in the old atria. The present study helps us to understand how the processes regulating atrial contraction are remodelled during ageing and provides a basis for future work aiming to understand why dysfunction develops.